The influence of the laterality of the lower limbs on the symmetry of connected carving turns - Vaverka, F.; Vodickova, S. (Science and Skiing IV, 2008)
INTRODUCTION: Laterality affects human motorics in both unilateral and bilateral movements. Right foot preference is manifested in approximately 80% of the overall population (Porac & Cohen, 1981). The influence of lateral preference on the quality of sport and basic movements has been investigated in several papers (e.g., Vaverka, 2005). Based on the personal experiences of skiers, we can assume that most of them favor either the turn to the right or the turn to the left. It can be expected that lateral preference with regard to the lower extremities can influence the quality of a ski turn to the right or left. We can also set up an alternative hypothesis and assume that there are no differences in the execution of a ski turn to the left and right in very experienced and long-term trained skiers.